2001
DOI: 10.1142/s0218348x0100066x
|View full text |Cite
|
Sign up to set email alerts
|

Singularity Features of Pore-Size Soil Distribution: Singularity Strength Analysis and Entropy Spectrum

Abstract: In this paper, several features of pore-size soil distribution are first analyzed, suggesting that they are closer to those of singular measures than to those of distributions with smooth density. In a second step, the weighted singularity strength of an experimental measure obtained by image analysis of soil samples is evaluated. The results of this analysis show the singular nature of pore-size distribution. Finally, the distribution is characterized by means of a spectrum of entropies computed on distorted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
55
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 31 publications
3
55
0
1
Order By: Relevance
“…Muller and McCauley (1992) were the first to characterize the multifractal behavior of the spatial arrangements Correspondence to: F. San José Martínez (fernando.sanjose@upm.es) of pore space in sedimentary rocks. Caniego et al (2001) observed the same pattern for the soil pore size distribution.…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…Muller and McCauley (1992) were the first to characterize the multifractal behavior of the spatial arrangements Correspondence to: F. San José Martínez (fernando.sanjose@upm.es) of pore space in sedimentary rocks. Caniego et al (2001) observed the same pattern for the soil pore size distribution.…”
Section: Introductionsupporting
confidence: 68%
“…Several works have explored the complex nature of soil porosity with multifractal analysis and they have established the suitability of this mathematical tool to characterize this highly irregular feature of soil with binarized images of sections of soil blocks (Muller and McCauley, 1996;Caniego et al, 2001;Posadas et al, 2003;Tarquis et al, 2003;García-Gutierrez and San José, 2004). Different techniques have been developed to acquire digitalized 2-D images.…”
Section: Introductionmentioning
confidence: 99%
“…(3)) and the Rényi generalized dimensions D q (Eqs. (4) and (5)) (Caniego et al 2001(Caniego et al , 2003. They were estimated via linear regression analysis with the least mean-square fit applying the power laws given in expressions (2), (3), (4) and (5).…”
Section: Estimation Of Multifractal Parametersmentioning
confidence: 99%
“…Multifractal analysis can be used to characterize the heterogeneous 2-D spatial arrangement of solid and void phases (Muller and McCauley, 1992;Posadas et al, 2003;Tarquis et al, 2003;Bird et al, 2006) and the complexity of pore size distribution (Caniego et al, 2001(Caniego et al, ,2003. These two, apriori, independent aspects can be modeled as mass distributions supported at a domain at a plane or at a size interval, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In soil science, the multifractal concept has been applied to analyze the pore size distribution and particles of soil [6][7][8], the image of a thin slice of soil [9], the structure of clay [10], the matrix pore structure of a porous medium [11], soil surface pressure [12] and soil spatial variability [13]. Muller and McCauley [4] were successful in applying the fractal method to characterize the properties of the fluid flow of sedimentary rocks.…”
Section: Introductionmentioning
confidence: 99%